ZFAS1 knockdown inhibits viability and enhances cisplatin cytotoxicity by up‐regulating miR‐432‐5p in glioma cells. Issue 6 (19th July 2019) - Yang, Gongli; Han, Banghua; Feng, Tao
Abstract: Background: Long non‐coding RNA (lncRNA) zinc finger antisense 1 (ZFAS1) is a novel vital oncogenic lncRNA that is dysregulated in various types of cancers, including glioma. According to TargetScan prediction, miR‐432‐5p is a target of ZFAS1. Herein, we aimed to determine whether there was a correlation between ZFAS1 and miR‐432‐5p and to explore their roles in glioma. Methods: The expression levels of ZFAS1 and microRNA (miR)‐432‐5p in clinical tissues and cell lines were measured using RT‐qPCR. Cell viability was detected using MTT assay. Cell apoptosis was examined using flow cytometry. The association between ZFAS1 and miR‐432‐5p was confirmed using luciferase reporter and RNA pull‐down assays. Results: Zinc finger antisense 1 expression was up‐regulated, while miR‐432‐5p expression was down‐regulated in both glioma tissues and cells. Knockdown of ZFAS1 and miR‐432‐5p overexpression inhibited cell viability and enhanced the chemosensitivity of glioma cells to cisplatin. MiR‐432‐5p was a direct target of ZFAS1 in glioma cells. Inhibition of miR‐432‐5p blocked the effects of ZFAS1 knockdown on cell viability and cisplatin sensitivity. Conclusions: Knockdown of ZFAS1 inhibited the viability and enhanced cisplatin sensitivity via targeting miR‐432‐5p in glioma cells.